A Study on Satisfaction and Influencing Factors of Educational Practice of Preschool Education Majors in Higher Vocational Colleges - Xiong, Jing; Kou, Heung; Zhang, Fang; Kong, Weifeng (Frontiers in Psychology, 2022)
In September 2020, the Ministry of Education and other nine departments issued the notice of "Action Plan for Improving the Quality of Vocational Education (2020-2023)" which emphasizes strong practical teaching. The state pays more and more attention to the quality of practical practice in higher vocational colleges. From the perspective of student satisfaction, this study explores the satisfaction of preschool education students on educational practice and related influencing factors, so as to better carry out educational practice and improve the quality of students' educational practice in colleges and universities. This study uses the questionnaire method, according to the existing literature and theory to build the results of self-compiled “higher vocational college students majoring in preschool education practice satisfaction and influencing factors questionnaire”. 463 students majoring in preschool education in higher vocational colleges were investigated. The following research results are obtained: The overall satisfaction of students majoring in preschool education in higher vocational colleges to educational practice is above the average. In descending order of satisfaction question scores, other factors influencing student’s satisfaction are the tutors in the educational practice park, the educational practice base, the content of educational practice, the management of educational practice, the tutors in the school of educational practice, and the time of educational practice. 2. For constructing the influencing factors model of educational practice satisfaction, it is found that the influencing factors of educational practice satisfaction are university management Rational factors, support factors from the educational base and students’ own factors.